Операция "Антитеррор": Роман / С. В. Самаров - Самаров С. В. (Спецназ ГРУ, 2003)
Экземпляры: аб. (20200123) / Инвентарный номер: 59959 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44